2018
DOI: 10.1111/jam.13727
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of foodborne bacteria by eosin Y

Abstract: This study evidenced the efficacy of photodynamic inactivation as a novel and promising alternative to bacterial control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 42 publications
(99 reference statements)
5
38
0
Order By: Relevance
“…Considering that the xanthenes used in the present study are in dianionic form (pH 7.4), it may be hypothesized that the presence of negative charges could reduce the interaction with Gram‐negative microorganisms. However, this is not a rule, once the results demonstrated in the present study and by several other authors have demonstrated that negatively charged PS can inactivate Gram‐negative bacteria . It has been suggested that anionic/neutral PSs accumulate close to the cell membrane in the extracellular environment.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the xanthenes used in the present study are in dianionic form (pH 7.4), it may be hypothesized that the presence of negative charges could reduce the interaction with Gram‐negative microorganisms. However, this is not a rule, once the results demonstrated in the present study and by several other authors have demonstrated that negatively charged PS can inactivate Gram‐negative bacteria . It has been suggested that anionic/neutral PSs accumulate close to the cell membrane in the extracellular environment.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these new methods should not induce the development of antimicrobial resistance [15][16][17]. Toward this end, antimicrobial photodynamic therapy (aPDT) has been considered as a promising non-antibiotic approach to inactivate foodborne bacteria [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This technique presents several advantages when compared with the use of traditional antimicrobials, showing to be efficient independently of the antimicrobial resistance profile and to prevent further development of resistance even after several cycles of treatment [15][16][17]26]. This approach has been efficient to inactivate several microorganisms, such as gram-negative and gram-positive bacteria [18,19,21], fungi [15,[27][28][29], and viruses [15,30], and to degrade the matrix of microbial biofilms and kill the resident bacteria [16,31,32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations